El Niño–Southern Oscillation Effects on Winter Wheat in the Southeastern United States. (1st November 2015) - Woli, Prem; Ortiz, Brenda V.; Johnson, Jerry; Hoogenboom, Gerrit
Abstract : The winter wheat ( Triticum aestivum L.) growing season in the southeastern United States occurs during the period when the climate of this region is strongly influenced by El Niño–Southern Oscillation (ENSO). The ENSO‐based interannual climate variability might influence growth, maturity, and yield of winter wheat. Because different maturity groups of wheat cultivars head at different times of the year, the groups are expected to have different impacts of climate variability. This study examined whether the yield difference between early and late maturity groups of winter wheat cultivars grown in this region were associated with ENSO‐based climate. Data on yield, planting date, and heading date were obtained for a number of wheat cultivars grown at four locations in Georgia during the 1975 to 2012 period. Wheat cultivars were classified according to heading date as early or late maturity, and yield differences between maturity groups and among ENSO phases were examined using the Wilcoxon rank sum test. Results showed that the early maturity group could out‐yield the late maturity group in southern locations during La Niña, whereas the late group could out‐yield the early group in northern locations during El Niño. Of all ENSO phases, La Niña was associated with the largest yields. During El Niño, the yield difference between early and late groups increased with an increase in latitude, whereas during La Niña, the yield difference increased with a decrease in latitude. These findings might be helpful to wheat growers in this region in optimizing decisions regarding planting date and cultivar selection to reduce the risks related to climate variability.